Multimodality Intra-Arterial Imaging Assessment of the Vascular Trauma Induced by Balloon-Based and Nonballoon-Based Renal Denervation Systems. (July 2015) - Karanasos, Antonios; Van Mieghem, Nicolas; Bergmann, Martin W.; Hartman, Eline; Ligthart, Jurgen; van der Heide, Elco; Heeger, Christian-H.; Ouhlous, Mohamed; Zijlstra, Felix; Regar, Evelyn; Daemen, Joost
<x xml:space="preserve">Abstract</x> Background— Renal denervation is a new treatment considered for several possible indications. As new systems are introduced, the incidence of acute renal artery wall injury with relation to the denervation method is unknown. We investigated the acute repercussion of renal denervation on the renal arteries of patients treated with balloon-based and nonballoon-based denervation systems by quantitative angiography, intravascular ultrasound, and optical coherence tomography (OCT). Methods and Results— Twenty-five patients (50 renal arteries) underwent bilateral renal denervation with 5 different systems, 3 of which balloon-based (Paradise [n=5], Oneshot [n=6], and Vessix V2 [n=5)]) and 2 nonballoon-based (Symplicity [n=6] and EnligHTN [n=3]). Analysis included quantitative angiography and morphometric intravascular ultrasound measurements pre and post procedure and assessment of vascular trauma (dissection, edema, or thrombus) by OCT after denervation. A significant reduction in lumen size by quantitative angiography and intravascular ultrasound was observed in nonballoon denervation but not in balloon denervation. By postdenervation OCT, dissection was seen in 14 arteries (32.6%). The percentage of frames with dissection was higher in balloon-based denervation catheters. Thrombus and edema were detected in 35 (81.4%) and 32 (74.4%) arteries, respectively. In arteries treated with balloon-based denervation that had dissection by OCT, the balloon/artery ratio was higher (1.24 [1.17–1.32] versus 1.10 [1.04–1.18]; P<0.01). Conclusions— A varying extent of vascular injury was observed after renal denervation in all systems; however, different patterns were identified in balloon-based and in nonballoon-based denervation systems. In balloon denervation, the presence of dissections by OCT was associated with a higher balloon/artery ratio.